(untitled) (Pedagogy of Higher and Secondary Education, 2022)
We propose to introduce the course „Methods of teaching Biology out-of-class activity” and also fulfillment of practical and scientific research tasks during teaching practice of students in the secondary school with the aim to improve the future teachers’ preparing for holding o f out-of class activity in Biology.